PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER RETENTION ORIENTATION DAN DAMPAKNYA PADA RELATIONSHIP OUTCOME DARI NASABAH BANK UMUM DI KOTA MALANG - Yustina - Chrismardani; Agung - Yuniarinto; Munawar - Ismail (Sekolah Pascasarjana Universitas Brawijaya, 2009)
ABSTRACT The relationship marketing consists of seven efforts, there are belonging, communication, customization, differentiation, personalization, rewarding, security and convenience. The purpose of this research are: 1) to analyze the significant direct effect of belonging, communication, customization, differentiation, personalization, rewarding, security and convenience on the customer retention orientation; 2) to analyze the significant direct effect of customer retention orientation on the relationship outcome; and 3) to analyze the significant indirect effect of belonging, communication, customization, differentiation, personalization, rewarding, security and convenience on the relationship outcome through the customer retention orientation. Results of this research are: 1) only belonging, communication, personalization, rewarding, security and convenience which have the significant direct effects on the customer retention orientation. Also found that customer retention orientation has a significant direct effect on the relationship outcome. It means that five variables mentioned above, have the significant indirect effects on the relationship outcome through the customer retention orientation; 2) customization and differentiation don’t have the significant direct effects on the customer retention orientation; so those don’t have the indirect effects on the relationship outcome through the customer retention orientation. The possibility of the reason why differentiation doesn’t have a significant effect is because this research doesn’t classify customers according to saving amount, so customers of this research are regular customers who probably don’t perceive the existence of differentiation on attention and special service provided by the bank. Perhaps customers also consider customization as an unimportant thing, but more consider a superior product, a hassle-free process (quick, briefly, simple, convenience) and an interaction with pleasant human resources (warm, polite, skillful, and helpful) as more important things.. Keywords : relationship marketing, customer retention orientation